2008
DOI: 10.1007/s00421-008-0738-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular fatigue is greater following highly variable versus constant intensity endurance cycling

Abstract: The present study compared neuromuscular fatigue of the knee extensor muscles following highly variable versus constant power output cycling. Ten subjects performed two 33-min cycling trials of the same average power output, in a random order. Cycling exercise was performed either at constant (CST) power output, corresponding to 70% of the maximal aerobic power (MAP), or at variable (VAR) power output with alternating high (200, 150 and 100% of MAP during 10, 15 and 20 s, respectively) and moderate (50% of MAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…41 In addition, the freely chosen cadence has been reported to be on average 9 rpm higher during cycling at variable power output compared with constant power output at a similar average power output of 70% of maximal aerobic power output. 42 A decrease in cadence with cycling duration has also been observed and is of unknown cause. [44][45][46][47][48] Perhaps the decrease in cadence has to do with fatigue of the neural networks constituting the central pattern generators or perhaps changed output from these.…”
Section: Draftingmentioning
confidence: 99%
“…41 In addition, the freely chosen cadence has been reported to be on average 9 rpm higher during cycling at variable power output compared with constant power output at a similar average power output of 70% of maximal aerobic power output. 42 A decrease in cadence with cycling duration has also been observed and is of unknown cause. [44][45][46][47][48] Perhaps the decrease in cadence has to do with fatigue of the neural networks constituting the central pattern generators or perhaps changed output from these.…”
Section: Draftingmentioning
confidence: 99%
“…Quantification of neuromuscular fatigue in various muscle groups after prolonged running and cycling exercises lasting 20 min to more thanLepers (2008) 33 min cycling with variations in power output (ergometer) Knee extensors -MVC maximal voluntary contraction, Pt peak twitch, Pd peak doublet, VL vastus lateralis, VM vastus medialis, NS not significant, -not measured…”
mentioning
confidence: 99%
“…These measures were not directly investigated in this study; however, it is probable that the higher intensity bout caused greater disruption to this mechanism. Alterations in SR functioning have been shown to relate to force development (Tupling et al 2000) and this was possibly demonstrated at the end of the fatigue test following high intensity exercise, with RTD and RR further decreased and remaining significantly lower than baseline and that following low intensity exercise. The significant level of lactate accumulation reported following the high intensity bout confirms a higher glycolytic demand placed on the muscle during high intensity work.…”
Section: Discussionmentioning
confidence: 93%
“…Whilst it is given that exercise intensity is an important parameter determining training response (Green et al 2004), to date the effect of exercise intensity on muscle contractile characteristics has not been clearly investigated Theurel and Lepers 2008). Specifically, to date no work has been conducted to investigate how muscle contractile characteristics respond to high and low intensity exercise, of the same average intensity.…”
Section: Introductionmentioning
confidence: 98%